Data from: A tool for determining duration of mortality events in archaeological assemblages using extant ungulate microwear - Rivals, Florent; Prignano, Luce; Semprebon, Gina M.; Lozano, Sergi (Zenodo, 2016)
The seasonality of human occupations in archaeological sites is highly significant for the study of hominin behavioural ecology, in particular the hunting strategies for their main prey-ungulates. We propose a new tool to quantify such seasonality from tooth microwear patterns in a dataset of ten large samples of extant ungulates resulting from well-known mass mortality events. The tool is based on the combination of two measures of variability of scratch density, namely standard deviation and coefficient of variation. The integration of these two measurements of variability permits the classification of each case into one of the following three categories: (1) short events, (2) long-continued event and (3) two separated short events. The tool is tested on a selection of eleven fossil samples from five Palaeolithic localities in Western Europe which show a consistent classification in the three categories. The tool proposed here opens new doors to investigate seasonal patterns of ungulate accumulations in archaeological sites using non-destructive sampling. DATASET 1 - EXTANT UNGULATES Dataset of tooth microwear patterns in large samples of 10 extant ungulate populations with good records of the date and conditions of death. DATASET 2 - ARCHAEOLOGICAL SAMPLES Dataset of tooth microwear patterns in archaeological samples of ungulates from five Middle and Late Pleistocene localities in Europe. Boundaries with transparent grid Transparent grid to be superimposed to the heat map for positioning new samples according the SD and CV values. Background with boundaries and error probability Boundary lines with the error probability (heat map) based on SD and CV values of microwear data used for the classification of samples into short events (region 1), long-continued events (region 2), or two separated short events (region 3). Background_with_boundaries_and_error_probability.tiff g12.dat Boundary between region 1 (short mortality events) and region 2 (longer mortality evens). The coordinates x (CV) and y (SD) of the ...